Pengaruh Citra Merek dan Harga terhadap Minat Beli Konsumen Jago Coffee di Jakarta Selatan - Shela Safirasuri; Ulta Rastyana (STIKes Ibnu Sina Ajibarang, 2024)
Jago Coffee is a retail business in the coffee shop industry that adopts the idea of Cafe on Wheels, a new idea in coffee sales. Yoshua Tanu, the owner of Coffee Jago, plans to do a rebranding in 2022. In addition to changes to the idea and design of the Jago Coffee electric wagon bicycle, customers can now order their drinks easily through this special app. The concept of a coffee shop around, which allows consumers to enjoy quality coffee at affordable prices, is very attractive and consumer in demand. The aim of the research is to identify and analyze the influence of brand image and price simultaneously on the interest of consumers to buy Jago coffee in South Jakarta. Using the questionnaire method for data collection as well as data processing using SPPS version 26 and its method of analysis is quantitative analysis, which is the method of statistical analysis. It is then known that brand image and price have a significant influence on buying interest. This research provides valuable insights for companies to optimize their marketing strategies by paying attention to brand image and price as key factors affecting consumer purchasing interests.